Stakeholder management and engagement in the utility industry - Dhawan, Rohit (2013)
Stakeholder management has become an increasingly important aspect of conducting business. Organizations no longer answer solely to their shareholders, but rather, a larger array of stakeholders in society. The same is true for utility companies. This paper discusses the shareholder/stakeholder debate, maps the various stakeholders relative to a utility company, and provides an example of a method of engagement with one of its’ stakeholders—the consumer.